1997
DOI: 10.1073/pnas.94.18.9938
|View full text |Cite
|
Sign up to set email alerts
|

VMAT2 knockout mice: Heterozygotes display reduced amphetamine-conditioned reward, enhanced amphetamine locomotion, and enhanced MPTP toxicity

Abstract: The brain vesicular monoamine transporter (VMAT2) pumps monoamine neurotransmitters and Parkinsonism-inducing dopamine neurotoxins such as 1-methyl-4-phenyl-phenypyridinium (MPP ؉ ) from neuronal cytoplasm into synaptic vesicles, from which amphetamines cause their release. Amphetamines and MPP ؉ each also act at nonvesicular sites, providing current uncertainties about the contributions of vesicular actions to their in vivo effects. To assess vesicular contributions to amphetamine-induced locomotion, amphetam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

25
313
1
4

Year Published

1998
1998
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 380 publications
(343 citation statements)
references
References 36 publications
25
313
1
4
Order By: Relevance
“…The high level of metab olites suggests an increase of both the time spent in the cytoplasm and the exposure to enzymes, such as monoamine oxidase (MAO), 29 as demonstrated by the increased 5-HT levels observed following MAO-A inhibition in VMAT2-KO mice. 11 The deletion of VMAT2 in DA neurons is solely responsible for postnatal death Whereas the constitutive deletion of VMAT2 is lethal 2-3 days after birth, [11][12][13] only its specific deletion in DA neurons reproduces this phenotype. Mice with a conditional deletion of VMAT2 in NE or 5-HT neurons are viable and reach adulthood, although retarded growth has previously been observed in VMAT2 SERTcre -KO mice.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The high level of metab olites suggests an increase of both the time spent in the cytoplasm and the exposure to enzymes, such as monoamine oxidase (MAO), 29 as demonstrated by the increased 5-HT levels observed following MAO-A inhibition in VMAT2-KO mice. 11 The deletion of VMAT2 in DA neurons is solely responsible for postnatal death Whereas the constitutive deletion of VMAT2 is lethal 2-3 days after birth, [11][12][13] only its specific deletion in DA neurons reproduces this phenotype. Mice with a conditional deletion of VMAT2 in NE or 5-HT neurons are viable and reach adulthood, although retarded growth has previously been observed in VMAT2 SERTcre -KO mice.…”
Section: Discussionmentioning
confidence: 99%
“…This increased locomotor response to drugs is associated with a decreased sensitization to cocaine and a reduction in amphetamine-conditioned place preference (CPP). 12,13 The behavioural characterization of VMAT2-HET and WT animals did not indicate any difference in anxiety levels, although a sucrose preference test revealed that HET mice are less responsive to sucrose. 14 In conjunction with the decreased CPP in HET mice, these data suggest the presence of anhedonia in VMAT2-HET mice.…”
Section: J Psychiatry Neurosci 2016;41(3)mentioning
confidence: 93%
See 1 more Smart Citation
“…Mice lacking both copies of the VMAT2 gene die during development, but heterozygotes survive and show reduced amphetamineconditioned reward, enhanced amphetamine and cocaineinduced locomotion, and enhanced MPTP toxicity (Takahashi et al, 1997;Wang et al, 1997). We hypothesized that sequence variants in the regions of the mouse genes encoding VMAT2, the alpha 2A adrenergic receptor, and/or beta-1 adrenergic receptor might explain the QTL and thus the differential effects of citalopram in the parental strains.…”
Section: Discussionmentioning
confidence: 99%
“…A paper by Silveira discusses a multidisciplinary approach to teaching students about the interplay of genes and the environment using a polymorphism that students were interested in but conveyed no risk for disease [9]. Following the submission of the paper, however, the author noted two recent reports that correlated VMAT2 variations with schizophrenia [30,31]. This raises a number of issues about how to deal with new developments after students have completed a genetic testing exercise.…”
Section: In the Classroommentioning
confidence: 99%